2000
DOI: 10.1111/j.1349-7006.2000.tb00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three‐month Oral Supplementation of β‐Carotene and Vitamin C on Serum Concentrations of Carotenoids and Vitamins in Middle‐aged Subjects: A Pilot Study for a Randomized Controlled Trial to Prevent Gastric Cancer in High‐risk Japanese Population

Abstract: Prior to a randomized controlled trial to prevent gastric cancer by oral supplementation of β β β β-carotene and vitamin C in a high-risk Japanese population, we examined the serum response to threemonth oral supplementation of β β β β-carotene (0, 3, 30 mg/day) and vitamin C (0, 50, 1000 mg/day) by a three-by-three factorial design using 54 subjects (age range = = = =40-69 years). Serum concentrations of carotenoids, α α α α-tocopherol, and ascorbic acid were examined at baseline, and one, two, and threemonth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Thus, the period for which subjects took the initial capsule ranges from 2 to 5 months. On the basis of the results of our pilot study (Sasaki et al, 2000), no statistically significant interaction between 3-month supplementation of b-carotene and vitamin C was seen either for serum bcarotene or for ascorbic acid. In fact, further adjustment for initial b-carotene treatment did not have any influence on the effect of vitamin C on common cold; adjusted RR and 95% CI for suffering from common cold three or more times during the survey period was 0.35 (0.12-0.97) in high-dose group.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Thus, the period for which subjects took the initial capsule ranges from 2 to 5 months. On the basis of the results of our pilot study (Sasaki et al, 2000), no statistically significant interaction between 3-month supplementation of b-carotene and vitamin C was seen either for serum bcarotene or for ascorbic acid. In fact, further adjustment for initial b-carotene treatment did not have any influence on the effect of vitamin C on common cold; adjusted RR and 95% CI for suffering from common cold three or more times during the survey period was 0.35 (0.12-0.97) in high-dose group.…”
Section: Discussionmentioning
confidence: 66%
“…High dose of b-carotene and vitamin C (Sasaki et al, 2000), the serum level of ascorbic acid acted simultaneously for the placebo and 50-mg supplemented groups; the percent changes in serum ascorbic acid from baseline for the placebo and 50-mg groups were 31 and 23% at 1 month, 37 and 23% at 2 months, and 31 and 29% at 3 months, respectively. In comparison with previous studies, the supplementation amount of 500 mg per day for the high-dose group in our study does not seem large.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, we set 500 mg as the dosage for the high-dose group. This amount of vitamin C is half of that which we tested in a pilot study (Sasaki et al 2000), in which no adverse effect was observed from taking 1000 mg vitamin C. In most randomized clinical trials of vitamin C, there was no apparent adverse effect of a higher dose of vitamin C (, 1000 mg/d). Results from other large intervention trials with higher doses of vitamin C suggest no evidence of any potential hazard with , 1000 mg/d (Brown et al 2001).…”
Section: Discussionmentioning
confidence: 84%
“…The vitamin C doses were set based on the pilot study (Sasaki et al 2000) in which we examined the serum response to 3-month oral supplementation of vitamin C (0, 50 or 1000 mg/d). In that study, the high-dose group (1000 mg/d) showed a significant increase in serum concentrations at each point during supplementation (1, 2 and 3 months), with no adverse effect.…”
Section: Methodsmentioning
confidence: 99%